The sweetness of life Southern planters at home - Genovese, Eugene D. 1930-2012 (Cambridge studies on the American South, 2017)
This book examines the home and leisure life of planters in the antebellum American South. Based on a lifetime of research by the late Eugene Genovese (1930–2012), with an introduction and epilogue by Douglas Ambrose, The Sweetness of Life presents a penetrating study of slaveholders and their families in both intimate and domestic settings: at home; attending the theatre; going on vacations to spas and springs; throwing parties; hunting; gambling; drinking and entertaining guests, completing a comprehensive portrait of the slaveholders and the world that they built with slaves. Genovese subtly but powerfully demonstrates how much politics, economics, and religion shaped, informed, and made possible these leisure activities. A fascinating investigation of a little-studied aspect of planter life, The Sweetness of Life broadens our understanding of the world that the slaveholders and their slaves made; a tragic world of both 'sweetness' and slavery